Asymmetry analysis of the arm segments during forward handspring on floor - Exell, T. A.; Robinson, G.; Irwin, G. (European Journal of Sport Science, 2016)
Asymmetry in gymnastics underpins successful performance and may also have implications as an injury mechanism; therefore, understanding of this concept could be useful for coaches and clinicians. The aim of this study was to examine kinematic and external kinetic asymmetry of the arm segments during the contact phase of a fundamental skill, the forward handspring on floor. Using a repeated single subject design six female National elite gymnasts (age: 19 ± 1.5 years, mass: 58.64 ± 3.72 kg, height: 1.62 ± 0.41 m), each performed 15 forward handsprings, synchronised 3D kinematic and kinetic data were collected. Asymmetry between the lead and non-lead side arms was quantified during each trial. Significant kinetic asymmetry was observed for all gymnasts (p < 0.005) with the direction of the asymmetry being related to the lead leg. All gymnasts displayed kinetic asymmetry for ground reaction force. Kinematic asymmetry was present for more gymnasts at the shoulder than the distal joints. These findings provide useful information for coaching gymnastics skills, which may subjectively appear to be symmetrical. The observed asymmetry has both performance and injury implications